Precision nutrition across climates: decoding diet, tradition, and genomic adaptations from South Asia to the Arctic - Pathak, Ajai Kumar; Kolesnikova, Anna; Sambreker, Deepika Uttam; Org, Elin; Kivisild, Toomas (Frontiers in Nutrition, 2025)
Human populations have developed distinct genetic adaptations to diet in response to changes in lifestyle and environments in which they live. Particularly contrasting patterns of dietary adaptations are expected in populations living in tropical versus extreme cold environments. This article explores the genetic, dietary, and microbiome-related adaptations in populations of South Asia and the Arctic. We review adaptations related to high-carbohydrate, plant-based diets in South Asians and compare these against adaptations in Arctic populations who have evolved to rely on fat- and protein-rich diets from marine and animal sources. We discuss how these genetic adaptations interact with traditional diets and microbiomes, and the implications for chronic disease risks as modern, westernized diets disrupt ancestral gene-diet-microbiome interactions. By comparing these regions, we highlight the need for genome-based nutrition created strategies that account for genetic diversity, local dietary traditions, and environmental context to promote precision health and prevent diet-related chronic diseases. This analysis offers new insights into how nutrition, culture, and genetics intersect in shaping population-specific health outcomes.